A Novel Cellulose-Preparation Method. Issue 1 (26th July 2018) - Gillespie, Richard
Abstract: The radiocarbon ( 14 C) dating of contaminated old wood has been seen as a challenge requiring many lengthy procedures, often using strong alkali extractions and carbon-containing solvents. Introduced here is a novel protocol called 2chlorOx, a twice-repeated sequence of alkaline hypochlorite and acidic chlorite oxidations, which is shown to work well for 14 C and 13 C measurements on both <5000 BP and >50, 000 BP wood samples, producing results superior to those from conventional acidic chlorite or acidic dichromate oxidations. The 2chlorOx method employs only inorganic reagents, many samples can be completed in less than one day under normal laboratory conditions, and cellulose prepared in this way is usually paper-white in color.